Problém reflexivity - Chaloupková, Lucie (Lidé města, 2024)
This article presents reflexivity in its various meanings and forms as it appears in anthropology and social sciences. During the second half of the twentieth century in these fields, it became both an inspiration for various theories of the functioning of social phenomena, but also a part of anthropological methodology: in the era of the reflexive turn, it served as a critique of the situatedness of the production of anthropological knowledge, which was supposed to unmask the personal influence of the researcher on the resulting form of the texts. Although the contribution of this stage to the understanding of the meaning of the textuality of anthropological works cannot be denied, I see its “normalization” as part of anthropological methodology as problematic. If we focus more closely on the functioning mechanisms of reflexivity and self-reflection, we will come across certain paradoxes. In this paper, I focus on various criticisms of reflexivity, through which I try to approach the essence of the problem of using reflexivity. Emphasis is placed on the debate on reflexivity as a pivotal mechanism in the organization of late modern societies as described by theorists such as Giddens, Beck, Lash or Archer. These theories are confronted with the concept of “speech” as understood by constructivist approaches such as discourse analysis, which view all meanings as variable and constantly constructed by linguistic means in ordinary speech. I further show how reflexivity is unmasked by the opponents of reflexive modernization theory as a rhetorical strategy used to legitimize the status quo. This example serves as an illustration of the illusory nature of reflexivity and the possibility of its misuse.